QUALITY OF MOBILE JKN APLICATION TO INCREASE HEALTH SERVICES ACCESS FOR JKN PARTICIPANTS IN PANDEMIC COVID-19 - Gusti Agung Sri Guntari; Ni Putu Ayu Wulan Noviyanti (JURNAL KESMAS DAN GIZI (JKG), 2022)
The National Health Insurance Program (JKN) is a social security organized by the government aimed at all Indonesians. Currently, BPJS Kesehatan as the organizing body of the JKN program has made a technological innovation, namely mobile JKN which is intended for its participants. This application is expected to make it easier for JKN participants to change participant data and access health services. During the Covid-19 pandemic like now, technology such as mobile JKN is an innovation that is the mainstay of society to reduce direct social interaction. Researchers feel that the effectiveness of the JKN mobile application is important to evaluate, to see the extent to which this application can help and facilitate public access to health services. This study used a qualitative method by conducting indepth interviews with 7 informants who were JKN participants and had used the JKN mobile application. Based on the results of the study, it can be stated that the JKN mobile application is very useful for JKN participants, especially during the Covid-19 pandemic. The use of the application is quite easy and has complete features. After the launch of the JKN mobile application, participants felt that the services received were more effective and efficient. However, there are still many features that have not been utilized by the public due to ignorance of the existence of these features.